Engineering technology curriculum development: bridging the gap between academia-industry through undergraduate final year project - Nurhidayah, Azmy; Ahmad Zairi, Mohd Zain (Human Resource Management Academic Research Society, 2018)
The Malaysia Higher Education sector has experienced major growth in the 60 years since its independence. In order for Malaysia to keep up with the increasingly challenging and competitive global economy, higher education must be sustainably transformed. One of the key shifts highlighted in the Malaysia Higher Education Blueprint 2015-2025 is through empowering Technology, Vocational, Education and Training (TVET) programmes. Although the graduates from the Malaysian Technical University Network (MTUN) have shown significant achievements through the Graduate Employability rates, there are some pressing issues that still need to be addressed. The industry practitioners have raised concerns about graduates that does not meet employers’ expectations and is not well-prepared to enter the workforce. As part of the initiative to address the gap above, the Engineering Technology Infrastructure Program (ETIM) at Universiti Malaysia Pahang (UMP) has taken the effort to appoint the industry practitioners as its Undergraduate Final Year Project (FYP) co-supervisors. These industry co-supervisors plays an important role since the beginning of the course by providing real-life industry problems for the students to propose solutions. This method have seen tremendous improvement towards students’ soft skills such as problem-solving and decision-making. This helps the graduates to better prepare themselves upon entering the workforce and simultaneously fulfilling the industry needs in being exposed to real-life industry problems. The industry and academia should continuously work together to ensure that the courses and curriculum are current and in accordance to the requirements posed by the industry.